2016
DOI: 10.1590/s1518-8787.2016050006180
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Brazilian People’s Pharmacy Program by older adults

Abstract: OBJECTIVE To assess the prevalence and factors associated with the use of the expanded Brazilian People’s Pharmacy Program among older adults and the reasons for not using it.METHODS In this population-based cross-sectional study conducted in the urban area of Pelotas, RS, Southern Brazil, we evaluated 1,305 older adults (aged 60 years or over) who had used medication in the last 15 days. Independent variables were socioeconomic factors, economic status, household income in minimum wages, educational attainmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
2
6
0
2
Order By: Relevance
“…Programs that provide free access to medications can contribute to the control and prevention of chronic diseases. 26 Regarding marital status, most of the respondents lived with a partner, which corroborates several other studies. 11,17,36,37,21,[26][27][28][29]32,34,35 Marital status can affect health service use, since married individuals seek health services more often, are more likely to receive a diagnosis and, consequently, obtain more information about and access to drug programs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Programs that provide free access to medications can contribute to the control and prevention of chronic diseases. 26 Regarding marital status, most of the respondents lived with a partner, which corroborates several other studies. 11,17,36,37,21,[26][27][28][29]32,34,35 Marital status can affect health service use, since married individuals seek health services more often, are more likely to receive a diagnosis and, consequently, obtain more information about and access to drug programs.…”
Section: Discussionsupporting
confidence: 87%
“…7,18,[21][22][23] However, most studies of this type have focused on urban populations, with few including both urban and rural populations. 9,11,17,[24][25][26][27][28][29][30] It can be inferred that, due to sociocultural and biological factors, women are more concerned with their health, take more medications, more regularly seek health services, and have more health programs specifically targeting them. 7,9,17,[31][32][33] In our sample, women were more frequent users of public pharmaceutical assistance programs, which contrasts with the results of a study that analyzed data from the 2008 National Household Sample Survey.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to the one reported in the VIGITEL 2011 study [ 21 ]. This finding may reflect a series of barriers that still exist, e.g., difficulty in scheduling a medical consultation to renew the prescription to be to obtain the medications, lack of knowledge about the list of medications available for free, prejudice against free medications provided by the government, and geographical limitations, among others [ 3 , 10 ]. For diabetes medications (oral and insulin), it was found that the main means of obtaining them in the North was private pharmacies, suggesting regional disparities in access.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy aims to promote the expansion of access to medication to the entire population. The purpose is to avoid withdrawal of treatment, especially by individuals with low income who use private health services, but have difficulty in buying the required medications in regular pharmacies [ 10 , 11 ]. The same questions were asked about diabetes medications.…”
Section: Methodsmentioning
confidence: 99%
“…When assessing access to different sources of medication, the main means of obtaining antihypertensive drugs in all regions was the private pharmacy. This nding may re ect a series of barriers that still exist, such as di culty in accessing the consultation for renewing the prescription for withdrawing medications, lack of knowledge about the list of medications available for free, prejudice against free medications provided by the government, and geographical limitations, among others 3,25 . For diabetes medications (oral and insulin), it was observed that the North, Northeast, and Midwest regions had private pharmacies as the main means of obtaining them, suggesting regional disparities in access.…”
Section: Discussionmentioning
confidence: 99%